1992
DOI: 10.1111/j.1365-2133.1992.tb00459.x
|View full text |Cite
|
Sign up to set email alerts
|

Bone changes and their significance in children with ichthyosis on long-term etretinate therapy

Abstract: Anxiety about the use of etretinate in children has been provoked by several reports describing skeletal abnormalities during long-term therapy. However, we have observed no evidence of skeletal toxicity in 42 children treated over an 11-year period. Radiological screening before and during treatment has failed to reveal abnormalities that would influence our decision to commence or to continue etretinate administration. We recommend that children who are to be treated with etretinate should have a baseline se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 32 publications
1
24
0
2
Order By: Relevance
“…Long-term use of systemic retinoids in children is associated with musculoskeletal side effects and premature epiphyseal closure, although studies so far have shown safety with the lower doses typically used, even for periods greater than 10 years. 47,[49][50][51][52] Nevertheless, we limit the duration of retinoid therapy in neonates to resolution of severe findings and we reserve long-term use of retinoids for adolescent and adult patients.…”
Section: Oral Retinoidsmentioning
confidence: 95%
“…Long-term use of systemic retinoids in children is associated with musculoskeletal side effects and premature epiphyseal closure, although studies so far have shown safety with the lower doses typically used, even for periods greater than 10 years. 47,[49][50][51][52] Nevertheless, we limit the duration of retinoid therapy in neonates to resolution of severe findings and we reserve long-term use of retinoids for adolescent and adult patients.…”
Section: Oral Retinoidsmentioning
confidence: 95%
“…However, prospective follow-up of 42 children treated over 11 years did not reveal any abnormalities that would significantly impede starting or continuing therapy. 110 Effects on growth have not subsequently been seen in a further 18 children treated with retinoids at Great Ormond Street Hospital (David Atherton, personal communication). If, in the opinion of the treating physician, the child's condition is severe enough to be physically, psychologically or socially incapacitating and such therapy is undertaken because the benefits outweigh the risks, then the child should be clinically monitored for any abnormalities of growth parameters and bone development.…”
Section: Skeletal Abnormalitiesmentioning
confidence: 99%
“…Најчешће пријављени нежељени ефекти су настанак остеофита и калцификација лигамената (21). С друге стране, Paige и сарадници нису приметили токсичне ефекте на скелет током студије у којој су лечили 42 детета у периоду од 11 година (22). Основа терапије подразумева свакодневно купање ради механичког отклањања сквама и превенирање суперинфекције.…”
Section: слика 3 локална обрада коже вазелинским газама и антибиотскunclassified